2021
DOI: 10.1002/ppap.202000104
|View full text |Cite
|
Sign up to set email alerts
|

Methanol synthesis from CO2 using Ni and Cu supported Fe catalytic system: Understanding the role of nonthermal plasma surface discharge

Abstract: The present study combines nonthermal plasma (NTP) and thermal catalysis to exploit the synergism for direct conversion of CO 2 to CH 3 OH using H 2 . Series of catalyst, that is, CuO/QW, NiO/QW, Fe 2 O 3 /QW, NiO/Fe 2 O 3 /QW, CuO/Fe 2 O 3 / QW have been tested for CO 2 conversion and CH 3 OH selectivity. And it was observed that 5 wt% CuO/Fe 2 O 3 /QW exhibited better CO 2 conversion and CH 3 OH selectivity as compared to other catalysts. With 5 wt% CuO/Fe 2 O 3 /QW, at200°C and 2-W NTP input power (100 ml/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…The bigger the NiO particle size the more difficult it is to reduce compared to small sized NiO particles, as hydrogen mass transfer is hindered. 34 2CO (ads) → C (ads) + CO 2 C (ads) + 2H 2(ads) → CH 4 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bigger the NiO particle size the more difficult it is to reduce compared to small sized NiO particles, as hydrogen mass transfer is hindered. 34 2CO (ads) → C (ads) + CO 2 C (ads) + 2H 2(ads) → CH 4 …”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we successfully showed that binary mixed metal oxides are more active towards CO 2 conversion and CH 3 OH production. 34 The main aim of this work was to employ mixed binary metal oxides of NiO–Fe 2 O 3 for the hydrogenation of CO 2 to CH 3 OH using non-thermal plasma. Dedicated efforts were made to investigate (i) the influence of individual and binary mixed metal oxides on CO 2 conversion and CH 3 OH production, (ii) the impact of NiO mixing on Fe 2 O 3 for CO 2 conversion and CH 3 OH selectivity, (iii) understanding the role that plasma power and operating temperature have on CO 2 conversion and products distribution, and (iv) the effect that plasma discharge has on catalyst surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…Joshi and Loganathan loaded CuO on quartz wool (QW) which was used as a catalyst in a modified plasma methanol synthesis. 18 In contrast to Wang et al, they introduced a heating furnace around the discharge area where the catalyst was loaded. They used stainless steel as the inner electrode and a stainless-steel mesh as the ground electrode (Figure 4).…”
Section: Cu-based Catalystsmentioning
confidence: 99%
“…NTP (or sometimes referred to as cold plasma) contains electrons, neutrals, electronically and vibrationally excited species, ions, radicals, and atoms. 18 The collision of these charged species with chemicals can catalyze the reactions such as bond dissociation or formation to take place at low temperatures and milder conditions than currently commercialized chemical processes. In contrast, the high temperature of thermal plasma makes it suitable for decomposition reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Developing a highly efficient CO 2 conversion technology is one crucial approach to alleviate the increasing energy crisis and achieve the goal of "carbon neutral". Direct CO 2 decomposition, [2,3] dry reforming of CH 4 , [4][5][6][7] CO 2 hydrogenation, [8][9][10][11] electrochemical reduction process, and solar thermochemical conversion of CO 2 with H 2 O [12] have been studied by many research groups. Among them, CO 2 hydrogenation is a promising solution to convert CO 2 into value-added chemicals, such as alcohols and hydrocarbons, because of the lower thermodynamic limitation.…”
Section: Introductionmentioning
confidence: 99%